(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the postoperative complications in patients underwent thyroidectomy at tertiary care Hospital Study Design: Prospective case series study Place and Duration of Study: This study was conducted at the Departments of General Surgery of LUH Hyderabad from October 2014 to September 2015. Materials and Methods: All the cases with diagnosis were thyroid disorder and underwent thyroidectomy were selected in the study. Cases above 25 years of age were included. Patients were prepared for the surgery after counseling regarding surgical and post-operative complications. All the surgeries were carried out by senior surgeons along with cooperation of the ENT surgeons. After surgeries patients were taken under follow-up and all developed postoperative complication were recorded in the proforma. Results: Mean age of the patients was 44.50+5.23 years. 31(43.66%) patients were male while 40(56.34%) were female. 100% patients had neck swelling, 8.45% had pain, 9.85% had swallow difficulty and 7.04% had breathing difficulty while othersless common complaints were found in 14.08% patients. Regarding post-operative complications, 4.22% patients had transient RNA palsy, 5.63% patients had hypocalcemia, 3.44% had dysphagia, 4.22% had infections, while 1.40% had seroma. Conclusion: Presentation of neck swelling was in all cases, and most common postoperative complications were hypocalcemia,transient RNA palsy and superficial infection, female gender is most common.